Corpo-nuance: a espetacularidade do k-pop a partir da trajetória de uma artista-etno-pesquisadora do Grupo Limitless de Belém do Pará - SOUSA, Ana Letícia Figueiró de (2021)
The present study deals with the spectacular nature of K-Pop in Belém of Pará, based on the trajectory of an artist-ethno-researcher, a practitioner of K-Pop culture in the artistic scenario of Para, using for analysis instruments both the personal trajectory of the author and the trajectory of K-Pop in a worldwide scope, focusing for its presence in Belém do Pará. Starting with the studies on Geertz's (1989) culture, the conception of cultural impregnation of Mendes (2010), and on the body’s investigation in the context of K-Pop in Belém of Pará, the concept of Body-Nuance is created. It displays Ethnocenology as the main theoretical basis and methodology as it focuses on highlighting the voice and conceptions of the subjects of the culture itself, having as instruments photographs, reports, observations made from the author, as teacher and dance artist. With the conclusion of this research, K-Pop is seen as an area of knowledge, both theoretical and practical, while it brings to these youngsters questions of learning, process composition, notions of body, with a look at the social relations present in this context . This research is for a better understanding of what K-Pop is and how it happens in that social niche that involves many young people.